Clinical predictive risk factors prolonged the duration of SARS-CoV-2 clearance in 279 moderate COVID-19 patients: A multicenter retrospective cohort study. Issue 40 (8th October 2021) - Wu, Xinxin; Zhou, Shuang; Liu, Changya; Huang, Tingrong; Zheng, You; Zhang, Wen; Qu, Yao; Fang, Bangjiang
Abstract : Abstract: The results of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) nucleic acid as one of the criteria has been widely applied to assess whether the coronavirus disease 2019 (COVID-19) patients could discharge, however, the risk factors that affect the duration of the SARS-CoV-2 clearance remained to be an enigma. Our research was to identify risk factors correlated with prolonged duration of the SARS-CoV-2 clearance in moderate COVID-19 patients. We retrospectively analyzed 279 consecutive ordinary COVID-19 patients in 3 hospitals in Hubei province including Huangshi Hospital of Infectious Disease, Wuhan Thunder God Mountain Hospital, and Tongji Hospital. Eight clinical characters were contained as risk factors. We used a logistic regression model and nomogram to assess the possibility that the SARS-CoV-2 nucleic acid may turn negative in 14 days. Time from symptoms onset to diagnosis (odds ratio [OR] = 3.18; 95% confidence interval [CI] 1.56–6.46; P = .001), time from onset use of antiviral drugs to onset of symptoms (OR = 0.41; 95% CI 0.23–0.72; P = .02), and bacterial coinfection (OR = 0.07; 95% CI 0.01–0.86; P = .038) were independent risks factors for the duration of SARS-CoV-2 nucleic acid clearance. The regression model showed good accuracy and sensitivity (area under the curve = 0.96). Nomogram was also provided to predict the negative conversion rate of SARS-CoV-2 nucleic acids within 14 days. Time from symptoms onset to diagnosi, time from onset use of antiviral drugs to onset of symptoms, and bacterial coinfection were independent risk factors for the time of SARS-CoV-2 nucleic acid turning negative in ordinary COVID-19 patients. However, the age, gender, underlying disease, fungal coinfection, and duration use of antiviral drugs were irrelevant factors. Abstract : Supplemental Digital Content is available in the text